Modality, Control and Restructuring in Arabic - (:unkn) unknown (My University, 2019)
The dissertation examines theories of modality and control with data from Standard Arabic (SA). In particular, I show that complementations of particular modal and control verbs in SA are not clausal, but smaller phrases. This challenges proposed accounts in the literature of modality in SA as well as theories of control within Minimalism. I alternatively argue for a novel account of both constructions that posits a monoclausal (i.e., restructuring) structure. First, Chapter 2 investigates modality verbs in SA and shows that subjunctive complements of modality do not exhibit the properties of clausal complementation. I examine the syntax-semantics properties of modality which reveal insights into the structure of modality. I argue that modality verbs are situated based on their semantic denotation. In this respect, I show that SA provides novel arguments to the long-held assumption that epistemic modality is high while root modality is low. Previously-unnoticed data are also discussed where it is shown that morphosyntactic properties comply with semantic restrictions that are independently motivated. Hence, I propose that modal verbs in SA have discrete positions in the clause structure and that they do not all target the same syntactic position. I discuss several arguments for this claim including Cinque’s (2001, 2006) hierarchy and its relative ordering. I present a novel analysis that posits that modality in SA is a restructuring (monoclausal) structure. The second part of the dissertation examines recent theories of control in Minimalism and argues that SA provides a new intriguing challenge in various theoretical and empirical aspects. In particular, I show that various empirical issues arise with the Movement Theory of Control (Hornstein, 2001; Boeckx and Hornstein, 2006, Hornstein et al., 2010), the Agree Theory of Control (Landau, 2000, 2004, 2006), and the Functional Theory of Control (Cinque, 2001, 2006; Grano, 2012). In Chapter 3, I establish that SA has obligatory control and examine the two types of control classified after Landau (2000). I argue that both Partial Control (PC) and Exhaustive Control (EC) obtain in SA. I propose a biclausal (i.e., non-restructuring) analysis for PC that postulates an embedded null syntactic subject (i.e., PRO). In Chapters 4 and 5, I provide a battery of restructuring diagnostics that show that EC in SA is restructuring and pose an enormous challenge to contrasting analyses. The chapters discuss various issues that pertain to theories of control and finite control crosslinguistically. In particular, it is shown that control theories that postulate biclausal constructions for EC make untenable predications and are thus empirically challenged. I propose a new restructuring analysis for EC in SA that derives its properties and does not encounter the empirical challenges observed with other theories. The proposed account has crosslinguistic consequences and also sheds new lights into the discrepancies between forward and backward control.
Keywords: Arabic; Control; Modality; Restructuring; Syntax; Syntax-semantics